Relationships between Physiochemical Properties in Water of Ain Kaam and Wadi Kaam in Zliten Libya. - Keri Ighwela (AlQalam Journal of Medical and Applied Sciences, 2020)
Background and Objective: The water sources have been affected in Libya since the beginning of the revolution in February 2011, including the Kaam area, which contains Ain Kaam (spring) and Wadi Kaam (dam), so the objective of this study was to observe the effect of war on the water of Ain Kaam and Wadi Kaam in Zliten Libya, and to determine the relationships between each other in physiochemical properties. Materials and Methods: Water samples were collected from both study sites during January and February 2018. The physical and chemical properties of all samples were evaluated which included pH, Electrical conductivity (EC), Total dissolved solids (TDS), Total hardness (TH), Calcium (Ca2+), Magnesium (Mg+2), Chloride (Cl-1), Sodium (Na+1), Potassium (K+1), Sulphate (SO4-2), and Bicarbonate (HCO3-1). All parameters analyzed according to standard methods. Results: The findings showed that values of pH, Electrical conductivity, total dissolved solids, calcium and potassium in the water of both study sites were within the permitted limits of Libyan standards and World Health Organization (WHO) for drinking and irrigation water. On the other hand, values of sodium, sulphate and bicarbonate were exceeded the acceptable limit in both study sites. It was also noted that, total hardness, magnesium and chloride exceeding the allowable values in Ain Kaam, while in Wadi Kaam were within the allowable values. Conclusion: The results of this study showed the physiochemical properties of water in both study sites were accepted for irrigation and need treatment for drinking.